2014
DOI: 10.1080/18334105.2014.11082024
|View full text |Cite
|
Sign up to set email alerts
|

Planning language teaching: An argument for the place of pedagogy in language policy and planning

Abstract: PedagogyWe master what others don't see, take time to make rough edges smooth, maintain tools of the trade, assemble and dissemble, polish, try again. We are the business of making ourselves obsolete, teaching studens to outstrip us, to sign their own pieces. Hard work that is never enough.Laurel Smith AbstractEven though pedagogy and language policy and planning are well researched and well-established fields in their own rights, the relationships between these two fields are not systematically addressed. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…A similar conclusion was made by researchers in Malayasia (Zahedpished, Abu Bakar, and Saffari, 2017), who argued that curricula in the international hospitality industry should be catered to the specific needs and wants of students, in actual situations where the language will be utilized. Finally, as Diallo and Liddicoat (2015) have argued, government officials also need to revise languagelearning policies at the national level, so that English is integrated into all educational curricula.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A similar conclusion was made by researchers in Malayasia (Zahedpished, Abu Bakar, and Saffari, 2017), who argued that curricula in the international hospitality industry should be catered to the specific needs and wants of students, in actual situations where the language will be utilized. Finally, as Diallo and Liddicoat (2015) have argued, government officials also need to revise languagelearning policies at the national level, so that English is integrated into all educational curricula.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The instructors' role is significant in influencing language policy in education positively or negatively. Diallo & Liddicoat (2015) indicate that language policy and language teaching (the implementation) are connected intricately. Teachers' profiles, training, attitudes are entangled in shaping their practices.…”
Section: Tamazight In the Algerian Schoolsmentioning
confidence: 99%
“…Language policy in the field of education often does not pay attention to readiness and implementation in society, which means that the facts about the English language eloquence of the community in welcoming the EMI program often do not meet the EMI application requirements in the university. However, policies have been taken to implement EMI (Diallo & Liddicoat, 2014). Araminta and Halimi (2015) reported that from the needs analysis carried out at the Faculty of Engineering at the University of Indonesia, it was concluded that students need a program which can develop their English skills not to teach them English.…”
Section: B Emi In Higher Education In Indonesiamentioning
confidence: 99%